GAMBARAN KESELAMATAN DAN KESEHATAN KERJA DALAM PENGGUNAAN PESTISIDA PADA PETANI SAYUR DI KELURAHAN LAMARU BALIKPAPAN - Marlina, Marlina; Ardi, Indrawan (Program Studi Kesehatan dan Keselamatan Kerja, 2019)
Lamaru Urban Village is one of the villages where the majority of the population earns a living as a vegetable farmer. to increase agricultural output farmers always use chemical pesticides to reduce pest attacks. Pesticides contain harmful chemicals. The use of PPE (Personal Protective Equipment) can protect farmers when mixing and spraying pesticides. This study aims to determine the description of occupational safety and health in the use of pesticides in vegetable farmers in Kelurahan Lamaru, Balikpapan, based on personal protective equipment and how spraying works. In this study using quantitative methods with the technique of saturated sample/total sampling. The method of data collection in this study was carried out by observation using univariate analysis which contains the frequency distribution to describe personal protective equipment and how it works. In fulfilling PPE farmers can only use a few PPE hats, long-sleeved clothes and long pants so that this is incompatible with PPE fulfilment and work methods because farmers' low level of education causes a lack of knowledge about the dangers of pesticides and farmers are in direct contact with pesticides without using PPE complete to cause acute poisoning with local effects namely itching and dizziness when spraying and after spraying. The concludes study of this study is that there is a description of occupational safety and health in the use of pesticides in vegetable farmers in the Mentari Jaya Farmer Group based on personal protective equipment as much as 38% and how to work as much as 57%.